2020
DOI: 10.1098/rsos.180191
|View full text |Cite
|
Sign up to set email alerts
|

Is mere exposure enough? The effects of bilingual environments on infant cognitive development

Abstract: Bilinguals purportedly outperform monolinguals in non-verbal tasks of cognitive control (the ‘bilingual advantage'). The most common explanation is that managing two languages during language production constantly draws upon, and thus strengthens, domain-general inhibitory mechanisms (Green 1998 Biling. Lang. Cogn. 1 , 67–81. ( doi:10.1017/S1366728998000133 )). However, this theory cannot explain why a bilingual advantage has been found in preverbal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(97 citation statements)
references
References 43 publications
(90 reference statements)
11
78
0
Order By: Relevance
“…However, 7-month-old infants do not produce words, so they do not need to inhibit words in one language in order to produce words in the other 9 . Moreover, when we tried to replicate Kovács and Mehler’s study but with a larger sample, we could not 10 . In our preregistered study 10 , infants from bilingual homes did indeed inhibit the learned response—but so too did infants from monolingual homes.…”
Section: Introductionmentioning
confidence: 88%
“…However, 7-month-old infants do not produce words, so they do not need to inhibit words in one language in order to produce words in the other 9 . Moreover, when we tried to replicate Kovács and Mehler’s study but with a larger sample, we could not 10 . In our preregistered study 10 , infants from bilingual homes did indeed inhibit the learned response—but so too did infants from monolingual homes.…”
Section: Introductionmentioning
confidence: 88%
“…Given its theoretical importance, there have been several attempts to replicate this initial finding. Five teams of researchers, testing infants between 7 and 10 months of age in tasks similar to the original study, did not observe differences between monolinguals and bilinguals (D'Souza et al, 2020;Ibánez-Lillo et al 2010;Kalashnikova, Pejovic, & Carreiras, 2020;Molnar, Pejovic, Yee, & Carreiras, 2014;Tsui & Fennell, 2019). However, in a variant of the paradigm that included more trials (60 rather than 18), Comishen and colleagues (2019) reported a bilingual advantage in one of two studies, after post-hoc exclusion of the first 10 and last 10 trials from analyses.…”
Section: Bilingual Advantage In Infancymentioning
confidence: 69%
“…The origins of such adaptations, moderators, and their impact later in life are interesting open questions. The present contribution was only possible because we employed a fine-grained moment-to-moment analytic approach that captured the richness of looking data and because of D'Souza et al (2020) and Kalashnikova et al's (2020) commitment to Open Science practices. We believe that largescale data collection from diverse bilingual infants, together with analyses that tap into the dynamics of infant learning, have a great potential to contribute to the complex and exciting debate of bilingualism effects in infancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations